Metafunctions Analysis of Instagram Meme in @9Gag Post - Ni Made Feby Pradnya Swari; Putu Nur Ayomi (CV Wahana Publikasi, 2024)
This study aims to analyze what language metafunctions appear in memes on the official 9GAG Instagram account and what representations appear in these language metafunctions. The research method used in this research is descriptive-analytical. Data processing is done by collecting data, analyzing the data, and then describing the data. The data sources are obtained via the Internet, and the last stage is to conclude the data. Based on the analysis results, the language metafunctions that appear in memes on the official 9GAG Instagram accounts include ideational, interpersonal, and textual components. The representations that emerge from the language metafunction are meme representations that refer to disseminating information, appreciation, and criticism to represent a certain character or event that is considered interesting, entertaining, and phenomenal. By using this mode, the reader will be able to understand the meaning and interpretation of the meme completely and thoroughly to absorb the information conveyed without any ambiguity.